1995
DOI: 10.1111/j.1365-2885.1995.tb00582.x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and tissue residues of norfloxacin and its N‐desethyl‐ and oxo‐metabolites in healthy pigs

Abstract: The pharmacokinetic properties of norfloxacin were determined in healthy pigs after single intramuscular (i.m.) and intravenous (i.v.) dosage of 8 mg/kg body weight. After i.m. and i.v. administration, the plasma concentration-time graph was characteristic of a two-compartment open model. After single i.m. administration, norfloxacin was absorbed rapidly, with a tmax of 1.46 +/- 0.06 h. The elimination half-life (t1/2 beta) and the mean residence time of norfloxacin in plasma were 4.99 +/- 0.28 and 6.05 +/- 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
41
5

Year Published

1999
1999
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 27 publications
5
41
5
Order By: Relevance
“…Our results were in agreement with previous studies which indicated that ciprofloxacin levels (an active metabolite of enrofloxacin) were too low in the plasma of pigs and enrofloxacin could be served as the marker for PK calculation (10,11). Based on the concentration-time curve of plasma enrofloxacin, a series of pharmacokinetic parameters for the 12 piglets were derived from a one-compartment model (see Table 1).…”
supporting
confidence: 79%
“…Our results were in agreement with previous studies which indicated that ciprofloxacin levels (an active metabolite of enrofloxacin) were too low in the plasma of pigs and enrofloxacin could be served as the marker for PK calculation (10,11). Based on the concentration-time curve of plasma enrofloxacin, a series of pharmacokinetic parameters for the 12 piglets were derived from a one-compartment model (see Table 1).…”
supporting
confidence: 79%
“…strain 4N2-2. NH 4 ϩ and NO 2 Ϫ at this concentration did not enhance the production of hydroxylated metabolites, but NO 3 Ϫ enhanced it even without ascorbic acid. The production of 8-hydroxynorfloxacin and 6-defluoro-6-dehydroxynorfloxacin in 14-day cultures in OM medium with 1.0 g liter Ϫ1 NaNO 3 was 78% and 56%, respectively, of the production in regular OM medium with 0.5 mM ascorbic acid (data not shown).…”
Section: Hplc Lc-esi-ms/ms and Nmr Analysesmentioning
confidence: 98%
“…The principal medium used, referred to as OM medium, was composed (per liter) of 1.0 g glucose, 50 mg NH 4 Enrichment cultures and strain isolation. Enrichment cultures (40 ml) in 250-ml flasks with 100 g ml Ϫ1 N-phenylpiperazine as the sole carbon source or nitrogen source were inoculated with aerobic liquor from a wastewater treatment plant in Little Rock, AR (28).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations